2001
DOI: 10.1021/ma001149y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PTHF-Grafted PMMA Based on the Reaction of Methyl Esters with Quaternary Ammonium Salts

Abstract: A new synthetic procedure is proposed to graft polymer chains onto poly(methyl methacrylate) based on the reaction of methyl esters with quaternary ammonium salts (MEQA reaction) under nonprotic conditions. Mechanistic insight into the MEQA reaction has been given by performing model reactions, for example with methyl benzoate and the N-butylammonium salt of 1,4-diazabicyclo[2.2.2]octane. This reaction has been used to graft poly(tetrahydrofuran) with a 1,4-diazabicyclo[2.2.2]octane end group, synthesized from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Alkyne-functionalized PTHF, the other "click" component, was prepared by terminating living PTHF chains with propargyl alcohol (Scheme 2), based on earlier developed synthetic routes for other end-functionalized PTHF systems. 47 As can be seen from Table 2, the molecular weights determined by GPC and 1 H NMR measurements were in good agreement with the theoretical ones, except for the higher molecular weight polymer. The observed difference may be attributed to the limits of the accuracy of estimation by 1 H NMR.…”
Section: Resultssupporting
confidence: 80%
“…Alkyne-functionalized PTHF, the other "click" component, was prepared by terminating living PTHF chains with propargyl alcohol (Scheme 2), based on earlier developed synthetic routes for other end-functionalized PTHF systems. 47 As can be seen from Table 2, the molecular weights determined by GPC and 1 H NMR measurements were in good agreement with the theoretical ones, except for the higher molecular weight polymer. The observed difference may be attributed to the limits of the accuracy of estimation by 1 H NMR.…”
Section: Resultssupporting
confidence: 80%
“…In a separate step, polymers that have been end-functionalized are prepared. These end-functionalized polymers are subsequently reacted covalently with the functional groups distributed along the original polymer backbone. , This approach allows the chains that eventually serve as branches to be characterized extensively before incorporation into the backbone and is often called the “grafting onto” approach.…”
Section: Introductionmentioning
confidence: 99%
“…Tong et al have demonstrated that a carboxylate anion can act as a nucleophile in an exchange reaction with onium ions at 140 °C, 11 and alkyl group displacements from quaternary ammonium halides by amine nucleophiles have been well documented. 12 We have similarly observed the ability of amines to participate in alkyl exchange with BPMN-derived compounds.…”
Section: Resultsmentioning
confidence: 99%